Channel selection in e-commerce age: A strategic analysis of co-op advertising models - Liu, Yongmei (OmniaScience, 2018)
The purpose of this paper is to develop and compare two co-op advertising models: advertising model under traditional channel and co-op advertising model under dual channel, to select optimal channel structure to sell products for manufacturer and to derive optimal co-op advertising strategies for the manufacturer and the retailer. Design/methodology/approach: Stackelberg game theoretical is used to develop two co-op advertising models: co-op advertising model under traditional channel and co-op advertising model under dual channel. Then we compare the two models to select optimal channel structure to sell products for manufacturer and to derive optimal co-op advertising strategies for the manufacturer and the retailer. Furthermore, we analyze the impact of product web-fit on these optimal strategies and illustrate by some numeral examples. Based on our results, we provide some significant theories and managerial insights, and derive some probable paths of future research. Findings: We provide a framework for researching optimal co-op advertising strategies in a two-level supply chain considering different marketing channel structures. First, we discuss the traditional channel co-op adverting model and the dual channel co-op advertising model based on Stackelberg game theoretical, and we derive optimal co-op advertising strategies. Next, comparisons of these two channel structures are discussed and we find that the manufacturer always benefits from dual channel. But the retailer not always benefits from dual channel structure, and dual channel structure is better than retail channel with certain conditions. Also, the optimal co-op advertising strategies for the manufacturer and the retailer are obtained. Research limitations/implications: First, we focus on the aforementioned two channel structures; a further comparison with other channel structures can be investigated. Second, we ignore some factors that influence the demand of product, such as service and price. We can do some researches from the point of these factors. Third, how demand uncertainty affects the channel selection and co-op advertising strategy is another interesting research item. Practical implications: The manufacturer and the retailer know that the impact of co-op adverting on the demands of traditional channel and direct channel, both would like to choose reasonable strategies to improve the channel coordination. Therefore, it would be best if business managers conduct market survey before they start their co-op advertising campaign. Originality/value: Two new co-op advertising models in E-commerce age are developed, and the impact of product web-fit on these optimal strategies are analyzed and illustrate by some numeral examples. In addition, optimal channel structure in E-commerce age are selected for manufacturer and the retailer